A high-hardness wear-resistant composite ceramic powder

By using composite ceramic powders combined with large particles WC and fine particles B4C, combining Cr, Ni, Fe as the matrix material, and performing laser cladding or plasma cladding processes, the problem of insufficient wear resistance and impact resistance of existing titanium-based composite powders under specific operating conditions is solved, and the preparation of high-hardness wear-resistant composite ceramic powder is achieved, which enhances the toughness and thermal shock resistance of the material, and reduces the cost.

CN118726811BActive Publication Date: 2025-04-22JIXI LONGXIANG NEW ENERGY TECH CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410723500.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-05
Publication Date
2025-04-22
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

In the mining and crushing operations of existing titanium-based composite powders under specific working conditions, such as hard rocks, wear resistance and impact resistance still need to be improved. At the same time, the material cost is high, which limits its wide application.

Method used

A high-hardness wear-resistant composite ceramic powder is prepared by combining large particles WC and fine particles B4C, combined with Cr, Ni, and Fe as the matrix material, and secondary processing is carried out through laser cladding or plasma cladding.

Benefits of technology

It significantly improves the wear resistance and impact resistance of composite ceramic powder, enhances the toughness and thermal shock resistance of the material, reduces costs, and expands its application range.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118726811B_ABST
    Figure CN118726811B_ABST
Patent Text Reader

Abstract

The invention discloses a high-hardness wear-resistant composite ceramic powder, comprising WC, B4C, Cr, Ni, C, Si, Mn, P, S and Fe, wherein the components are calculated by weight percentage as follows: B4C 3-12wt%, Cr 5.4-9wt%, Ni 2.4-5.4wt%, C 0.01-0.02wt%, Si 0.3-0.45wt%, Mn 0.5-0.9wt%, P 0.01-0.02wt%, S 0.01-0.02wt% and Fe 22-30wt%. %, and the balance is WC; the beneficial effects of the present invention are: the combination of large-particle WC and fine-particle B4C significantly improves the wear resistance and impact resistance of the composite ceramic powder, and is suitable for hard rock working conditions; the addition of B4C enhances the toughness of the composite material, reduces the thermal stress during temperature changes, and improves the thermal shock resistance; Cr, Ni, and Fe are used as matrix materials to ensure good material metallurgical properties and mechanical properties; secondary processing can be performed through laser cladding or plasma cladding technology, thereby expanding its application range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ceramic powders, and in particular relates to high-hardness wear-resistant composite ceramic powder. Background Art

[0002] Composite ceramic powder is an industrial product, mainly a powder system formed by mixing or compounding various high-melting-point hard ceramic materials such as carbides, nitrides, borides, oxides and silicides with metals; this powder has the characteristics of wear resistance, corrosion resistance, high strength and high melting point under specific conditions.

[0003] Metal powder cladding wear-resistant layer is prone to produce electric sparks during operation, and fire accidents may occur during the operation.

[0004] A high-hardness, wear-resistant spherical titanium-based composite powder and a preparation method thereof are disclosed with publication number CN114713832B. The patent discloses that titanium-based material and ceramic powder are mixed evenly and allowed to stand to obtain a mixed powder; the mixed powder is subjected to vacuum hot pressing and sintering treatment to obtain a titanium-based composite material; and the titanium-based composite material is subjected to rotary pulverization to obtain a high-hardness, wear-resistant spherical titanium-based composite powder.

[0005] Although titanium-based composite powders have certain wear resistance, they often reduce the material's toughness and thermal shock resistance; under specific working conditions, such as mining and crushing of hard rocks, their wear resistance and impact resistance still need to be improved; in addition, the high cost of titanium-based materials limits their widespread application. Summary of the invention

[0006] The object of the present invention is to provide a high-hardness wear-resistant composite ceramic powder, which not only has excellent wear resistance and impact resistance, but also has good toughness and thermal shock resistance.

[0007] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a high-hardness wear-resistant composite ceramic powder, comprising WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, wherein the components are calculated by weight percentage: B4C3-12wt%, Cr5.4-9wt%, Ni2.4-5.4wt%, C0.01-0.02wt%, Si0.3-0.45wt%, Mn0.5-0.9wt%, P0.01-0.02wt%, S0.01-0.02wt%, Fe22-30wt%, and the balance is WC.

[0008] As a preferred technical solution of the present invention, it includes WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, and its components are as follows by weight percentage: WC 59.5wt%, B4C 5.1wt%, Cr 6.8wt%, Ni 3.4wt%, C 0.011wt%, Si 0.35wt%, Mn 0.7wt%, P 0.02wt%, S 0.019wt%, and Fe 24.1wt%.

[0009] As a preferred technical solution of the present invention, it includes WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, and its components are as follows by weight percentage: WC 49.19wt%, B4C 9.8wt%, Cr 7.6wt%, Ni 4.1wt%, C 0.012wt%, Si 0.36wt%, Mn 0.8wt%, P 0.018wt%, S 0.015wt%, and Fe 28.105wt%.

[0010] As a preferred technical solution of the present invention, it includes WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, and its components by weight percentage are: WC 42.19wt%, B4C 12wt%, Cr 9wt%, Ni 5.4wt%, C 0.02wt%, Si 0.45wt%, Mn 0.9wt%, P 0.02wt%, S 0.02wt%, and Fe 30wt%.

[0011] As a preferred technical solution of the present invention, the WC is large particles with a diameter of 0.4-0.5 mm.

[0012] As a preferred technical solution of the present invention, the B4C is fine particles filled in the gaps between WC particles.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] The combination of large WC particles and fine B4C particles significantly improves the wear resistance and impact resistance of the composite ceramic powder, making it suitable for hard rock working conditions.

[0015] The addition of B4C enhances the toughness of the composite material, reduces the thermal stress during temperature changes, and improves the thermal shock resistance;

[0016] Using Cr, Ni and Fe as matrix materials ensures good metallurgical and mechanical properties of the material;

[0017] It can be processed by laser cladding or plasma cladding to expand its application range. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1This is a photo of the distribution of hardness test points of the cross section after laser cladding in Example 1 of the present invention;

[0019] Figure 2 This is a photo of the distribution of hardness test points of the cross section after laser cladding in Example 2 of the present invention;

[0020] Figure 3 This is a photograph of the distribution of large particles of tungsten carbide in a cross section after laser cladding in Example 1 of the present invention;

[0021] Figure 4 This is a diagram showing the enrichment of large-particle tungsten carbide of the present invention;

[0022] Figure 5 This is a photo of the structure of the joint of different cladding layers in Example 1 of the present invention;

[0023] Figure 6 A photograph of the structure of the junction between the cladding layer and the substrate in Example 1 of the present invention;

[0024] Figure 7 This is a second photo of the structure of the junction between the cladding layer and the substrate in Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] Example 1

[0027] See also Figure 1 and Figure 4 , is the first embodiment of the present invention, which provides a high hardness and wear-resistant composite ceramic powder, including WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, and its components are as follows by weight percentage: WC 59.5wt%, B4C 5.1wt%, Cr 6.8wt%, Ni 3.4wt%, C 0.011wt%, Si 0.35wt%, Mn 0.7wt%, P 0.02wt%, S 0.019wt%, and Fe 24.1wt%.

[0028] Element WC <![CDATA[B4C]]> Cr Ni C Si Mn P S Fe wt% 59.5 5.1 6.8 3.4 0.011 0.35 0.7 0.02 0.019 24.1

[0029] In this embodiment, preferably, WC is tungsten carbide, and tungsten carbide adopts large particles with a diameter of 0.5 mm; it can improve the wear resistance and impact resistance of the material to hard rock conditions; improve the material's high temperature resistance performance; and improve the hardness of the material.

[0030] In this embodiment, preferably, B4C is boron carbide, and fine particles of boron carbide are used, which are filled in the gaps between large particles of tungsten carbide after cladding to improve the wear resistance of the substrate and the toughness of the substrate material; since boron carbide has a low thermal expansion coefficient, it can enhance the thermal shock resistance and toughness of the ceramic powder, reduce the damage to the wear-resistant material caused by impact, and increase the service life; boron carbide can reduce the thermal stress during temperature changes, so as to ensure that the iron-based material does not crack during cladding, and greatly reduce the damage to the substrate structure caused by the shedding and cracking of the wear-resistant material during the operation; the low density of boron carbide makes it easier to evenly distribute the large particles of tungsten carbide in the cladding layer during the metal powder cladding process, ensuring that the overall cladding layer metal has high wear resistance and high toughness and high strength; the addition of low-cost boron carbide reduces the amount of expensive tungsten carbide, thereby improving the economic benefits; improving the density of the cladding metal, thereby reducing the weight of the operating tool and increasing the economic benefits.

[0031] In this embodiment, preferably, the base material adopts Cr, Ni, Fe alloy with high toughness and high weldability to ensure good material metallurgical properties and mechanical properties: high hardness, high wear resistance and high toughness.

[0032] In this embodiment, preferably, there are two methods for preparing and using the composite ceramic powder: the first method is to mechanically mix all the powders and then directly feed the powders for cladding; or to mix the powders other than WC and feed the mixed powders and WC powders into the molten pool separately during cladding;

[0033] The second method is to sinter the mixed powder with good ratio under vacuum hot pressing, and then use mechanical breaking, ball milling and particle size screening methods to obtain metallurgically treated composite powder;

[0034] The first preparation and use method is to determine the proportion and particle size of each component according to the performance requirements of the cladding layer, then weigh each group of raw materials, and mix them mechanically to obtain a uniformly dispersed mixed powder; the second preparation and use method is to determine the proportion and particle size of each component according to the performance requirements of the cladding layer, then weigh each group of raw materials, and mix them mechanically, and perform vacuum hot pressing and sintering on the mixed powder to obtain a preliminary composite material; the preliminary composite material is crushed and sieved to obtain a composite ceramic powder with uniform particle size; the composite ceramic powder obtained by the two preparation methods can be clad by laser or plasma heat source as needed, and the first powder cladding process is selected to match the powder (the heat source heat cannot be too large, and the power parameters should be selected to ensure that the large particles of tungsten carbide are not completely dissolved and other powders are fully dissolved. Cladding processing is performed to ensure the presence of large particles of tungsten carbide and thus ensure wear resistance); laser cladding, plasma cladding and other methods can also be used to feed different powders through two or more powder feeders;

[0035] The composite ceramic powder can be processed by laser cladding or plasma cladding process as needed; laser cladding is used with two powder feeders, one for feeding large particles of tungsten carbide and the other for feeding small particles of other powders. The diameter of large particles of tungsten carbide is 0.5mm, and the particle size of other powders is 0.12mm.

[0036] like Figure 1 As shown, the distribution photos of hardness test points on the cross section after laser cladding, and the hardness test data table are as follows:

[0037] Test location 1 2 3 4 5 6 7 8 9 10 11 average value Hardness / HRA 88.5 85.3 85.3 88.9 88.9 110.1 81.9 82.5 77.4 83.8 84.6 87.0

[0038] like Figure 1 , 3 As shown in the figure, after laser cladding, a microstructure consisting mainly of large tungsten carbide particles is formed in the cladding layer, and other materials such as boron carbide are filled in the gaps between the large tungsten carbide particles.

[0039] like Figure 5 As shown, the microstructure photos of the joints of different cladding layers in Example 1 show that the layers are well bonded to each other and to the substrate, without defects such as unfused layers and cracks.

[0040] like Figure 6 As shown in FIG. 1 , a microstructure photograph of the junction between the cladding layer and the substrate in Example 1; Figure 7 As shown in Figure 2, the second photo of the organization of the junction of the cladding layer and the substrate in Example 1; from the photo, the junction of the cladding layer and the substrate is a fine columnar crystal perpendicular to the bonding surface, which gradually transitions to a uniform and fine needle-like structure toward the cladding layer. This organizational distribution provides an effective guarantee for the high hardness and high wear resistance of the material.

[0041] Example 2

[0042] See also Figure 2 , is the second embodiment of the present invention, which provides a high hardness and wear-resistant composite ceramic powder, including WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, and its components are as follows by weight percentage: WC 49.19wt%, B4C 9.8wt%, Cr 7.6wt%, Ni 4.1wt%, C 0.012wt%, Si 0.36wt%, Mn 0.8wt%, P 0.018wt%, S 0.015wt%, and Fe 28.105wt%.

[0043] Element WC <![CDATA[B4C]]> Cr Ni C Si Mn P S Fe wt% 49.19 9.8 7.6 4.1 0.012 0.36 0.8 0.018 0.015 28.105

[0044] In this embodiment, preferably, WC is tungsten carbide, and tungsten carbide adopts large particles with a diameter of 0.45 mm; it can improve the wear resistance and impact resistance of the material to hard rock conditions; improve the material's high temperature resistance performance; and improve the hardness of the material.

[0045] In this embodiment, preferably, B4C is boron carbide, and fine particles of boron carbide are used, which are filled in the gaps between large particles of tungsten carbide after cladding to improve the wear resistance of the substrate and the toughness of the substrate material; since boron carbide has a low thermal expansion coefficient, it can enhance the thermal shock resistance and toughness of the ceramic powder, reduce the damage to the wear-resistant material caused by impact, and increase the service life; boron carbide can reduce the thermal stress during temperature changes, so as to ensure that the iron-based material does not crack during cladding, and greatly reduce the damage to the substrate structure caused by the shedding and cracking of the wear-resistant material during the operation; the low density of boron carbide makes it easier to evenly distribute the large particles of tungsten carbide in the cladding layer during the metal powder cladding process, ensuring that the overall cladding layer metal has high wear resistance and high toughness and high strength; the addition of low-cost boron carbide reduces the amount of expensive tungsten carbide, thereby improving the economic benefits; improving the density of the cladding metal, thereby reducing the weight of the operating tool and increasing the economic benefits.

[0046] In this embodiment, preferably, the base material adopts Cr, Ni, Fe alloy with high toughness and high weldability to ensure good material metallurgical properties and mechanical properties: high hardness, high wear resistance and high toughness.

[0047] In this embodiment, preferably, there are two methods for preparing and using the composite ceramic powder: the first method is to mechanically mix all the powders and then directly feed the powders for cladding; or to mix the powders other than WC and feed the mixed powders and WC powders into the molten pool separately during cladding;

[0048] The second method is to sinter the mixed powder with good ratio under vacuum hot pressing, and then use mechanical breaking, ball milling and particle size screening methods to obtain metallurgically treated composite powder;

[0049] The first preparation and use method is to determine the proportion and particle size of each component according to the performance requirements of the cladding layer, then weigh each group of raw materials, and mix them mechanically to obtain a uniformly dispersed mixed powder; the second preparation and use method is to determine the proportion and particle size of each component according to the performance requirements of the cladding layer, then weigh each group of raw materials, and mix them mechanically, and perform vacuum hot pressing and sintering on the mixed powder to obtain a preliminary composite material; the preliminary composite material is crushed and sieved to obtain a composite ceramic powder with uniform particle size; the composite ceramic powder obtained by the two preparation methods can be clad by laser or plasma heat source as needed, and the first powder cladding process is selected to match the powder (the heat source heat cannot be too large, and the power parameters should be selected to ensure that the large particles of tungsten carbide are not completely dissolved and other powders are fully dissolved. Cladding processing is performed to ensure the presence of large particles of tungsten carbide and thus ensure wear resistance); laser cladding, plasma cladding and other methods can also be used to feed different powders through two or more powder feeders;

[0050] The composite ceramic powder can be processed by laser cladding or plasma cladding process as needed; laser cladding is used with two powder feeders, one for feeding large particles of tungsten carbide and the other for feeding small particles of other powders. The diameter of large particles of tungsten carbide is 0.45mm, and the particle size of other powders is 0.15mm.

[0051] like Figure 2 As shown, the distribution photos of hardness test points on the cross section after laser cladding, and the hardness test data table are as follows:

[0052] Test location 1 2 3 4 5 6 7 8 9 10 11 average value Hardness / HRA 84.1 80.6 82.6 60.9 86.5 85.7 86 71 86.4 86.1 83.4 81.2

[0053] Example 3

[0054] See also Figure 1 and Figure 2 , is the third embodiment of the present invention, which provides a high hardness and wear-resistant composite ceramic powder, including WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, and its components are as follows by weight percentage: WC42.19wt%, B4C12wt%, Cr9wt%, Ni5.4wt%, C0.02wt%, Si0.45wt%, Mn0.9wt%, P0.02wt%, S0.02wt%, and Fe30wt%.

[0055] Element WC <![CDATA[B4C]]> Cr Ni C Si Mn P S Fe wt% 42.19 12 9 5.4 0.02 0.45 0.9 0.02 0.02 30

[0056] In this embodiment, preferably, WC is tungsten carbide, and tungsten carbide adopts large particles with a diameter of 0.4 mm; it can improve the wear resistance and impact resistance of the material to hard rock conditions; improve the material's high temperature resistance performance; and improve the material's hardness.

[0057] In this embodiment, preferably, B4C is boron carbide, and fine particles of boron carbide are used, which are filled in the gaps between large particles of tungsten carbide after cladding to improve the wear resistance of the substrate and the toughness of the substrate material; since boron carbide has a low thermal expansion coefficient, it can enhance the thermal shock resistance and toughness of the ceramic powder, reduce the damage to the wear-resistant material caused by impact, and increase the service life; boron carbide can reduce the thermal stress during temperature changes, so as to ensure that the iron-based material does not crack during cladding, and greatly reduce the damage to the substrate structure caused by the shedding and cracking of the wear-resistant material during the operation; the low density of boron carbide makes it easier to evenly distribute the large particles of tungsten carbide in the cladding layer during the metal powder cladding process, ensuring that the overall cladding layer metal has high wear resistance and high toughness and high strength; the addition of low-cost boron carbide reduces the amount of expensive tungsten carbide, thereby improving the economic benefits; improving the density of the cladding metal, thereby reducing the weight of the operating tool and increasing the economic benefits.

[0058] In this embodiment, preferably, the base material adopts Cr, Ni, Fe alloy with high toughness and high weldability to ensure good material metallurgical properties and mechanical properties: high hardness, high wear resistance and high toughness.

[0059] In this embodiment, preferably, there are two methods for preparing and using the composite ceramic powder: the first method is to mechanically mix all the powders and then directly feed the powders for cladding; or to mix the powders other than WC and feed the mixed powders and WC powders into the molten pool separately during cladding;

[0060] The second method is to sinter the mixed powder with good ratio under vacuum hot pressing, and then use mechanical breaking, ball milling and particle size screening methods to obtain metallurgically treated composite powder;

[0061] The first preparation and use method is to determine the proportion and particle size of each component according to the performance requirements of the cladding layer, then weigh each group of raw materials, and mix them mechanically to obtain a uniformly dispersed mixed powder; the second preparation and use method is to determine the proportion and particle size of each component according to the performance requirements of the cladding layer, then weigh each group of raw materials, and mix them mechanically, and perform vacuum hot pressing and sintering on the mixed powder to obtain a preliminary composite material; the preliminary composite material is crushed and sieved to obtain a composite ceramic powder with uniform particle size; the composite ceramic powder obtained by the two preparation methods can be clad by laser or plasma heat source as needed, and the first powder cladding process is selected to match the powder (the heat source heat cannot be too large, and the power parameters should be selected to ensure that the large particles of tungsten carbide are not completely dissolved and other powders are fully dissolved. Cladding processing is performed to ensure the presence of large particles of tungsten carbide and thus ensure wear resistance); laser cladding, plasma cladding and other methods can also be used to feed different powders through two or more powder feeders;

[0062] The composite ceramic powder can be processed by laser cladding or plasma cladding process as needed; laser cladding is used with two powder feeders, one for feeding large particles of tungsten carbide and the other for feeding small particles of other powders. The diameter of large particles of tungsten carbide is 0.4mm, and the particle size of other powders is 0.18mm.

[0063] Although the embodiments of the present invention have been shown and described, as detailed above, it will be understood by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high hardness and wear-resistant composite ceramic powder, characterized in that: It includes WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, and its components are calculated by weight percentage: B4C 3-12wt%, Cr 5.4-9wt%, Ni2.4-5.4wt%, C0.01-0.02wt%, Si0.3-0.45wt%, Mn0.5-0.9wt%, P0.01-0.02wt%, S0.01-0.02wt%, Fe22-30wt%, and the balance is WC. B4C uses fine particles and is filled in the gaps between large WC particles after B4C cladding.

2. The high hardness and wear-resistant composite ceramic powder according to claim 1, characterized in that: It includes WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, and its components by weight percentage are: WC 59.5wt%, B4C 5.1wt%, Cr 6.8wt%, Ni 3.4wt%, C 0.011wt%, Si 0.35wt%, Mn 0.7wt%, P 0.02wt%, S 0.019wt%, Fe 24.1wt%.

3. The high hardness and wear-resistant composite ceramic powder according to claim 1, characterized in that: It includes WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, and its components by weight percentage are: WC 49.19wt%, B4C 9.8wt%, Cr 7.6wt%, Ni 4.1wt%, C 0.012wt%, Si 0.36wt%, Mn 0.8wt%, P 0.018wt%, S 0.015wt%, Fe 28.105wt%.

4. The high hardness and wear-resistant composite ceramic powder according to claim 1, characterized in that: It includes WC, B4C, Cr, Ni, C, Si, Mn, P, S, and Fe, and its components by weight percentage are: WC 42.19wt%, B4C 12wt%, Cr 9wt%, Ni 5.4wt%, C 0.02wt%, Si 0.45wt%, Mn 0.9wt%, P 0.02wt%, S 0.02wt%, and Fe 30wt%.

5. A high hardness wear-resistant composite ceramic powder according to any one of claims 1 to 4, characterized in that: The WC is large particles with a diameter of 0.4-0.5 mm.

6. The high hardness and wear-resistant composite ceramic powder according to claim 5, characterized in that: The B4C is fine particles with a particle size of 0.12-0.18 mm.

7. The high hardness and wear-resistant composite ceramic powder according to claim 1, characterized in that: There are two methods for preparing and using composite ceramic powders: the first is to mechanically mix all the powders and then directly send the powders for cladding; or to mix other powders except WC, and send the mixed powders and WC powders into the molten pool separately during cladding; the second is to vacuum hot press sinter the mixed powders with a good ratio, and then use mechanical breakage, ball milling, and particle size screening methods to obtain metallurgically treated composite powders.

Citation Information

Patent Citations

  • A high-hardness wear-resistant spherical titanium-based composite powder and preparation method thereof

    CN114713832B

  • WC-fe-based cemented carbide, and method for producing same

    WO2010093136A2